Nano-Engineered Surface Comprising Metallic Dendrites for Biomolecular Analysis in Clinical Perspective - Kumari R.; Dkhar D.S.; Mahapatra S.; Divya S.; Singh S.P.; Chandra P. (My University, 2025)
Metallic dendrites, a class of three-dimensional nanostructured materials, have drawn a lot of interests in the recent years because of their interesting hierarchical structures and distinctive features. They are a hierarchical self-assembled array of primary, secondary, and terminal branches with a plethora of pointed ends, ridges, and edges. These features provide them with larger active surface areas. Due to their enormous active areas, the catalytic activity and conductivity of these nanostructures are higher as compared to other nanomaterials; therefore, they are increasingly used in the fabrication of sensors. This review begins with the properties and various synthetic approaches of nanodendrites. The primary goal of this review is to summarize various nanodendrites-engineered biosensors for monitoring of small molecules, macromolecules, metal ions, and cells in a wide variety of real matrices. Finally, to enlighten future research, the limitations and future potential of these newly discovered materials are discussed. © 2022 by the authors.